Women Political Participation in Nigerian General Election: An Overview on The Role of Non-Governmental Organizations - Chinazo Destiny Ewuru; Ku Hasnita Ku Samsu; Lee Yok Fee (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 10 Issue 2 Page (116–123)